mig-21 regulates Wnt signaling in the DTC. - Xin Li (51274) (2025)
(A) Micrographs: DIC imaging of C. elegans hermaphrodites at the late larval L4 stage, comparing wild type N2 (left) and mig-21(u787) (right) under RNAi control L4440 empty vector, mom-5 RNAi, lin-17 RNAi, or egl-20 RNAi feeding treatment to assess DTC migration defect phenotypes. Images are Z-projections through 2-3 μm showing the distal gonad. Anterior left and ventral down. Black dashed lines outline gonads. Yellow asterisks mark DTC; yellow carets mark the proximal vulval position. Scale bar: 20 μm. (B) All DTC migration defects across experimental groups, including wild type N2 (gray) and mig-21(u787) (black) strains, under RNAi control L4440 empty vector (wild type n=102; mig-21(u787) n=253), Frizzled receptors mom-5(wild type=202; mig-21(u787) n=150) and lin-17(wild type n=125; mig-21(u787) n=138) and Wnt ligands egl-20 (wild type n=110; mig-21(u787) n=131), lin-44 (wild type n=20; mig-21(u787) n=22), mom-2(wild type n=58; mig-21(u787) n=64), cwn-1 (wild type n=23; mig-21(u787) n=39), cwn-2 (wild type n=29; mig-21(u787) n=45) RNAi feeding treatments. Significant enhancements of migration defects by mig-21(u787) were observed in mom-5, lin-17, egl-20, and mom-2 groups. (C) DTC migration defects for the groups with significant enhancement by mig-21(u787) in anterior (left) and posterior (right) arms. Lighter one means wild type groups, darker one means mig-21(u787) groups. (B-C) All sample sizes refer to individual worms. On the graphs, “no defect” means no defect observed in that group. Error bars represent the standard error of the sample proportion. Statistical analysis was performed using a pairwise proportion test, with p-values adjusted for multiple comparisons via the Benjamini-Hochberg procedure. Significant differences are indicated between groups where applicable. ****p < 0.0001; ***p < 0.001; **p < 0.01; *p < 0.05; no mark means the comparison was not statistically significant. The corresponding sample sizes and statistics are presented in Tables E–J in S1 File; additional details like raw data collections, calculated means, and SEM are presented in Sheets E-F in S2 File.